Exploring the molecular underpinnings of neuropathic pain in primary afferent subtypes - Barry, AM (2022)
Dorsal root ganglia (DRG) neurons have been well described for their role in driving both acute and chronic pain. With cell bodies clustered in the spinal column, these neurons project from the periphery into the dorsal horn. Subtypes convert a range of stimuli into electrical signals, and have been traditionally defined by size, histological markers, projection pathways, and electrophysiological phenotypes. With the advance of sequencing technologies, DRG transcriptomes have been examined through whole ganglia, single cell, and more recently, deep subpopulation sequencing in naïve lines. Here, we study the deep transcriptional profiles of multiple murine DRG populations in acute and chronic pain states while considering sex interactions.